(untitled) (Global Journal of Human-Social Science, 2012)
This paper examined teacher parent student factors and job opportunities as determinants of students choice of History of Education in selected universities in Nigeria An expo facto research design was adopted 108 respondents were sampled from the 3 selected universities from Northern Western and Earthen Nigerian A self-designed questionnaire was used to elicit in formation from the sampled respondents and data collected were coded and analyzed in line with the four generated esearch hypotheses using Person Product Moment Correlation Co-efficient The findings show that teacher parent student factors and job opportunities are determinants of students choice of History of Education in the Nigerian Universities At last recommendation such as the need for National Universities Commission to enforce law for all the universities in Nigeria offering teacher education programme to employ experts in History of Education to teach the course as this will improve the students interest in the course and provide for the experts in the field